'Narrow-sense' and 'broad-sense' vascular abnormalities of systemic sclerosis. Issue 3 (2nd July 2020) - Jinnin, Masatoshi
Abstract: Systemic sclerosis (SSc) induces skin thickening and numerous symptoms involving the entire body. Collagen deposition, immune disorder, and vascular abnormalities is currently estimated to be three major causal factors involved in the respective conditions. Vascular abnormalities usually develop in the initial phase of this disease, and may exist in all phases; therefore, they markedly influence the patient's quality of life. This article reviews recent findings about 'narrow-sense' vascular lesions (including Raynaud's phenomenon, skin ulcers, nailfold bleedings, pitting scars, telangiectasia, and pulmonary hypertension) and 'broad-sense' vascular lesions (such as calcinosis or erectile dysfunction). Affected blood vessels can be classified into arteriole/small artery and capillary blood vessels. Furthermore, pathological changes include the proliferation of the vascular endothelial or smooth muscle cells, lumen stenosis by collagen accumulation of the vascular intima, vasodilation or fragility, and apoptosis. There may be interaction between vascular lesions, autoimmune disorder, and collagen deposition. Thus, various symptoms of this disease may be controlled through the treatment of vascular lesions.